Inheriting Cultural Heritage: The Application of Virtual Reality Technology in the Display of Peking Opera Costumes - Zhiyan Su (IEEE Access)
Peking Opera costumes, as an essential visual emblem of traditional Chinese opera culture, encapsulate profound national aesthetics and socio-cultural significance. However, within contemporary communication contexts, conventional exhibition methods are often inadequate to elicit strong cognitive and emotional engagement from audiences. In this study, we develop an immersive presentation system for Peking Opera costumes using virtual reality (VR) technology, aiming to reconstruct the costumes’ cultural context and visual semiotic framework through multi-sensory interaction and situational re-creation. During system development, level-of-detail (LOD) management and occlusion culling techniques were incorporated to optimize model rendering efficiency and ensure smooth platform performance. On the exhibition side, a multimodal interface combined with semantic-parsing mechanisms was implemented to enhance user engagement and deepen cultural comprehension. Performance testing demonstrates that, while preserving high visual fidelity, the system significantly improves interaction efficiency and immersion. This work offers a viable pathway and technical foundation for the digital preservation and presentation of intangible cultural heritage.